Racial Uplift and American Music, 1878-1943 - Schenbeck, Lawrence (Book collections on Project MUSE., 2012)
Racial Uplift and American Music 1878-1943 traces the career of racial uplift ideology as a factor in elite African Americans' embrace of classical music around the turn of the previous century, from the collapse of Reconstruction to the death of composer/conductor R. Nathaniel Dett, whose music epitomized "uplift." After Reconstruction many black leaders had retreated from emphasizing "inalienable rights" to a narrower rationale for equality and inclusion: they now sought to rehabilitate the Race's image by stressing class distinctions, respectable middle-class behavior, a.